Educating Compassionate Attitudes: Perkampungan Sosial Pingit as a Mode for Public Theology - Amadea Prajna Putra Mahardika; Jakobus Aditya Christie Manggala; Paulus Bambang Irawan (Proceedings of The International Conference on Theology, Religion, Culture, and Humanities, 2024)
This paper discusses the concept of public theology, which involves dialogue and engagement with society, aiming for social justice, community welfare, and the common good for the world. It emphasizes the necessity for public theology to address issues affecting the wider community and to use language and logic understandable and debatable by the public. Although aligned with political and liberation theology, public theology tends to be more reformative than revolutionary. The Perkampungan Sosial Pingit (PSP) in Yogyakarta demonstrates concrete involvement in social work, reflecting public theology. This research highlights the engagement of PSP volunteers, the relationship between emotional impulse and compassion, and the impact of social involvement on religion and theology. Furthermore, it shows how social activism and theology influence and enrich each other, providing inspiration for the involvement of young people in social work and public theology.